Collective skill systems, wage bargaining, and labor market stratification - Busemeyer, Marius R. [Verfasser]; Iversen, Torben [Verfasser] (My University, 2012)
The study of labor market stratification, in particular income inequality, is at the core of comparative political economy. "The influential work by Goldin and Katz (2007, 2008) argues that rising levels of inequality are caused by skill-biased technological change (SBTC). This chapter, in contrast, claims that the institutional setup of the training system and the centralization of collective wage bargaining are two important factors shaping the impact of SBTC and, therefore, labor market stratification. Using a sample of OECD countries from 1980 until 2000, we find that a strong involvement of firms in vocational training, when accompanied by high levels of bargaining centralization, decreases youth unemployment. Public investments in vocational training are less effective in reducing youth unemployment, but have a diminishing impact when combined with strong bargaining centralization. Furthermore, public investments in training are more strongly associated with decreasing wage dispersion than firm involvement. We find evidence for an inverted U-shaped relationship: when bargaining centralization is at either low or high levels, public investments in VET are most effective in reducing wage inequality. The effect is smaller in magnitude when bargaining is semi-decentralized, because in this case the benefits of public investments drive up the wages of skilled workers relative to those of unskilled workers." The contribution provides some explorative, descriptive statistics and delves into a quantative analysis of the determinants of labor market stratification. (BIBB-Doku, Autorenreferat)
Keywords: S System beruflicher Bildung; G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; S 2.1.6 Arbeits- & Tarifrecht; G 1.2.2.4 Arbeitslosigkeit; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; Berufsbildungssystem; Technischer Wandel; Qualifikationswandel; Tarifvertrag; Ausbildungsbeteiligung; Bildungsfinanzierung; Soziale Ungleichheit; Jugendarbeitslosigkeit; Einkommensverteilung; Einkommensunterschied